Development of Orthopedic Implants: Tribological Insights and Biomedical Material Innovations in Mechanical Engineering - Deshmukh, Harshal Panditrao; Shekhawat, Sanjay Pratapsingh; Goswami, Ajaygiri K. (Journal of Neonatal Surgery, 2025)
This comprehensive review paper concentrates on tribocorrosion behavior of biomaterials and composites in the context of orthopedic implant applications. This review paper focuses on the wear behavior of hip implant materials in the context of orthopedic implant applications. It highlights the critical importance of understanding the effects of different lubrication mediums on wear characteristics and emphasizes the necessity for comprehensive tribological investigations to optimize lubrication conditions for improved implant longevity and performance. Through an in-depth analysis of engineering studies, the paper highlights the crucial role of material characterization methods such as scanning electron microscopy and X-ray diffraction in assessing the microstructure and chemical composition of biomaterials for implant suitability. Mechanical testing techniques are explored to evaluate the tensile strength, flexural strength, and hardness of biomaterials, crucial for determining their performance in implant systems. The review emphasizes the significance of materials like Polyetheretherketone (PEEK), Ultra-High Molecular Weight Polyethylene (UHMWPE), carbon fiber-reinforced resins, and titanium alloys in enhancing the mechanical properties and longevity of orthopedic implants. Furthermore, advancements in additive manufacturing techniques for creating customized structures for biomedical applications are discussed. The paper concludes by stressing the importance of interdisciplinary research in optimizing the design and performance of biomaterials for orthopedic implants, ultimately aiming to enhance implant longevity and overall performance